AMERICAN AND INDONESIAN IMPERATIVE SENTENCES: POLITENESS IN NEWS MEDIA - Tridinanti, Gaya; Sari, Farnia (English Community Journal, 2022)
This study aims to analyze the differences and similarities in the imperative politeness of American and Indonesian in the news media. Descriptive qualitative research was used. Data were collected from the news column in The Jakarta Post and Kompas. The research used qualitative approach. The results showed that American and Indonesian imperative sentences have differences that are the position of American politeness marker can be at the beginning or at the end of the sentence, while in Indonesian politeness marker can only be placed at the beginning of the sentence. Moreover, American and Indonesian imperative sentences of politeness in news media have similarities that are the use of the basic form of the verb at the beginning of a sentence; a statement about the desire for one's public self-image in the form of involvement and endorsement to get respect from others; and polite statement based on the face compensation amount.